Immigrants, Communists, and Solidarity Unionism in Niagara, c. 1930–1960 - Patrias, Carmela (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2018)
Focusing on the Niagara region, this study explains the continued adherence of thousands of Canadian workers to communist-led unions during the Cold War era. It argues that co-operation between communist-led unions and communist-led ethnic clubs and other political and social activists in the pursuit of human rights, social justice, and environmental goals explains why thousands of workers continued to adhere to such unions despite intense redbaiting in the 1940s and 1950s. Reaching out to allies beyond the workplace in solidarity unionism was especially important because of the marginalization of communist-led unions within the Canadian labour movement. The study’s findings reinforce the view that local economic and political conditions played a significant role in shaping communist-led unions in Canada. The study also highlights the contribution of interethnic collaboration among immigrant workers to the development of the Canadian labour movement.